Dampak Pola Asuh Strict Parents terhadap Perkembangan Psikologis Anak - Rodia Tammardiah Hasibuan; Daman Daman; Sasmiyarti Sasmiyarti; Dewi Fitriana (Departement of Mathematics Education, 2024)
Parenting styles play a crucial role in the psychological development of children. This study aims to explore the impact of strict parenting on children's psychological development, focusing on aspects such as self-esteem, stress, anxiety, and behavioral problems. The findings indicate that children raised in strict parenting environments tend to experience lower self-esteem, higher levels of stress and anxiety, and more frequent behavioral issues compared to children raised with a more balanced parenting approach. Specifically, these children often feel unable to meet their parents' high expectations and fear punishment if they fail, leading to decreased self-confidence and self-worth. The high levels of stress and anxiety in these children are also associated with the pressure to always perform perfectly and the fear of negative consequences for mistakes. This study highlights the importance of balance in parenting, where discipline is accompanied by emotional support and open communication. Consequently, children can develop into confident, mentally healthy individuals capable of positive social interactions. These findings provide insights for parents, educators, and policymakers to design more effective parenting and educational strategies to support children's psychological development.